Intrinsic Complex Vacancy-Induced d0 Magnetism in Ca2Nb2O7 PLD Film - Wu, Linjie; Zhang, Yongjia; Nie, Zhongquan; Cao, Ensi (Frontiers in Materials, 2021)
Introducing magnetism into the ferroelectric Ca2Nb2O7 with high Curie temperature can make it a potential multiferroic material at room temperature. Stoichiometric Ca2Nb2O7, nonstoichiometric Ca1.9Nb2O7-δ and Ca2Nb1.9O7-δ single phase films were deposited on STO (110) substrate by pulsed laser deposition under appropriate conditions. The films were characterized by XRD, FE-SEM, Element mapping and XPS. Both stoichiometric Ca2Nb2O7 and Ca1.9Nb2O7-δ films were diamagnetic in the magnetic measurement and ab initio calculations, while the Ca2Nb1.9O7-δ film with the complex vacancy of VNb+O exhibited ferromagnetic behavior at room temperature, with the saturated magnetization of 3.6 emu/cm3. Calculations on the Ca2Nb2O7 (010) surface indicate that the VNb+O can induce spin polarization on the residual O atoms around the Nb vacancies, and the system was most stable when the Nb and O vacancies were the 4th nearest-neighbored, with FM coupling energetically more stable than the AFM coupling. Our work verified experimentally and theoretically the feasibility of introducing ferromagnetism into Ca2Nb2O7 film by the intrinsic complex vacancy of VNb+O.